Pengaruh Tarif Pajak, Kepercayaan Penggunaan Dana, dan Pemahaman Akuntansi terhadap Kepatuhan Pajak Melalui Religiusitas - Herman Herman; Randy Chaidir; Fitri Arliani (Politeknik Ganesha Medan, 2025)
This research examines taxpayer compliance in Micro, Small and Medium Enterprises using three independent variables, namely tax rates, confidence in the use of funds, and understanding of accounting. What is used as an intervening variable is religious characteristics. The research was carried out by distributing questionnaires to Micro, Small and Medium Enterprises in Balikpapan. The total number of questionnaires distributed was 115 and 88 samples met the requirements for processing. The method used is regression analysis using SmartPLS 3 software. This research found that there is a positive but not significant effect of the tax rate variable on tax compliance, trust in the use of funds has a positive and significant effect on tax compliance, accounting understanding has a positive and significant effect on tax compliance. , religiosity has a positive but not significant effect on tax compliance, while religiosity, when it is an intervening variable, has no effect on tax compliance. Tax rates have no effect on tax compliance through religiosity, trust in the use of funds has no effect on tax compliance through religiosity, and understanding accounting has no effect on tax compliance through religiosity. This shows that a person's religious nature is not able to have an impact on taxpayers' perceptions of the tax rates applied by the government, it does not have an impact on taxpayers' perceptions of integrity and government policies, religious nature has no impact on taxpayers' perceptions of increasing their accounting knowledge. on taxpayer compliance in paying taxes